Prohibition of Women Wearing Hijab in Work (Descriptive Study of the Prohibition of Women Wearing Hijab in Work in Surabaya City) - Dwina Rastri Juniar Krisanti (International Journal of Religion, Humanity and Cultural Heritage, 2025)
This research focuses on the phenomenon of women who are required to remove their hijab due to job demands in Surabaya City. Discrimination in work requirements that mandate removing the hijab has caused controversy to this day. Many still consider that companies or workplaces do not tolerate women who are Muslim women wearing hijab, arguing that their work environment is a public place, not a mosque where hijab must be worn in the office or while working. The main objective of this research is to understand the factors that influence women's decisions to remove their hijab when working and to identify the impacts of women's decisions to remove their hijab. The method used in this research involved interviewing several selected sources to delve deeper into the decisions made. This research also used literature analysis and library studies relevant to the latest research developments. This research uses alienation theory proposed by Karl Marx. The research results show that factors such as social pressure, perceptions of professional image, and company policies affect these decisions. The impacts vary, including changes in coworker relationships and changes in women's identity.